An EOQ Model with Stock and Time Dependent Consumption Rate with Shortages under Inflationary Environment - Rajoria, Yogendra Kumar; Saini, Seema; Chauhan, Anand (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*282.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934602);" role="presentation">In this paper, <span dir="ltr" style="left: calc(var(--scale-factor)*129.14px); top: calc(var(--scale-factor)*282.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901501);" role="presentation">we deve<span dir="ltr" style="left: calc(var(--scale-factor)*162.62px); top: calc(var(--scale-factor)*282.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934834);" role="presentation">loped an Economic order quantity model for decaying goods <span dir="ltr" style="left: calc(var(--scale-factor)*414.31px); top: calc(var(--scale-factor)*282.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946617);" role="presentation">with stock and time <span dir="ltr" style="left: calc(var(--scale-factor)*497.86px); top: calc(var(--scale-factor)*282.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941666);" role="presentation">reliant <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*296.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923841);" role="presentation">demand rate under inflationary <span dir="ltr" style="left: calc(var(--scale-factor)*199.85px); top: calc(var(--scale-factor)*296.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922781);" role="presentation">environment <span dir="ltr" style="left: calc(var(--scale-factor)*253.49px); top: calc(var(--scale-factor)*296.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935084);" role="presentation">and time discounting over a f<span dir="ltr" style="left: calc(var(--scale-factor)*372.67px); top: calc(var(--scale-factor)*296.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940939);" role="presentation">ixed <span dir="ltr" style="left: calc(var(--scale-factor)*392.95px); top: calc(var(--scale-factor)*296.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935668);" role="presentation">time <span dir="ltr" style="left: calc(var(--scale-factor)*413.71px); top: calc(var(--scale-factor)*296.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899041);" role="presentation">horizon. Shortages are also <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*309.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911645);" role="presentation">permitted and are partially backordered<span dir="ltr" style="left: calc(var(--scale-factor)*230.33px); top: calc(var(--scale-factor)*309.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897811);" role="presentation">. The results are discussed with a numerical example and particular cases <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89458);" role="presentation">are also di<span dir="ltr" style="left: calc(var(--scale-factor)*113.18px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912548);" role="presentation">scussed briefly.